VD_FINDINFO Jug / 2017 / 137 vom 28. April 2014 - VD Tribunal cantonal (2014)
TORT MORAL, DÉTENTION INJUSTIFIÉE, INDEMNITÉ POUR DÉTENTION, INDEMNITÉEN GÉNÉRAL, DOMMAGES-INTÉRÊTS | 28 CC, 49 CO, 73 al. 1 CO, 429 CPP (CH)